Total Ergonomic Approach in Decreasing Quality of Fatigue of Metal Crafters - Adiatmika, I Putu Gede (ANIMA Indonesian Psychological Journal, 2009)
Overtime work condition can create work related fatigue caused by stress. Work condition im- provement could decrease quality of fatigue of the employees. A total ergonomic approach (TEA) was conducted to decrease the quality of fatigue of metal crafters at Kediri Tabanan. Samples (N = 23) were chosen randomly from the population. Fatigue was measured through a modification of 30 items questionnaire from the Industrial Fatigue Research Committee. Results show a 9.22% (p < 0.05) decrease in fatigue, revealing that decrease of motivational fatigue is higher than decrease in fatigue due to physical activity, due to the type of work: manual, repetitive, and continuous. It was suggested to use TEA continuously to decrease the fatigue and maintain motivation. Kondisi kerja lembur dapat menimbulkan kelelahan sebagai salah satu akibat stres. Perbaikan kondisi kerja diharapkan menurunkan kualitas kelelahan karyawan. Sebuah pendekatan ergonomi total telah dilaksanakan untuk mengetahui perubahan kualitas kelelahan perajin logam di Kediri Tabanan. Sampel sejumlah 23 orang dipilih secara acak dari populasi. Kelelahan diukur dengan modifikasi 30 butir kuesioner model Industrial Fatigue Research Committee. Hasil-hasil menunjukkan penurunan kelelahan sebanyak 9.22% (p < 0.05) dan menunjukkan bahwa penurunan kelelahan motivasi lebih banyak daripada kelelahan aktivitas fisik, mengingat jenis pekerjaan yang manual, repetitif, dan berkelanjutan. Disarankan pendekatan ergonomi total diteruskan untuk menurunkan kelelahan dan mempertahankan motivasi kerja karyawan.